1970
DOI: 10.54155/jbs.5.1.31-39
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Assessment of The Relationship Between Management Levels and Planning Among Small Business Practitioners

Abstract: Planning in small businesses has been the subject of considerable research. Virtually every issue of the Strategic Management Journal contains at least one article dedicated to that subject. Numerous researchers have found that planning activities improve organizational pedormance (i.e., [17J, [22J, [15J, [26J, [27], [28]), but there is not uniform agreement in support of this conclusion (i.e. [5], [8], [18], [3]). Neither can scholars agree as to how organizational performance should be measured [19]. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
0
0
4
Order By: Relevance
“…O objetivo deste capítulo é discutir e apresentar um modelo teórico que defina um estilo de funcionamento cognitivo-comportamental para o empreendedor, considerando a Teoria Motivacional de Maslow. Na literatura do empreendedorismo, há comumente constructos pouco explorados ou não explorados suficientemente, como é o caso dos processos meta-cognitivos da autorrealização do indivíduo empreendedor (Akilu;Junaidu, 2015;Carland;Carland;Carland III, 1995;. Uma parte dos estudiosos trabalha o empreendedorismo como catalisador de mudanças na economia, através de inovações tecnológicas e novos processos de produção Oliveira, 2016).…”
Section: Rafael Farias Gonçalves Gustavo Henrique Silva De Souza Nilt...unclassified
See 1 more Smart Citation
“…O objetivo deste capítulo é discutir e apresentar um modelo teórico que defina um estilo de funcionamento cognitivo-comportamental para o empreendedor, considerando a Teoria Motivacional de Maslow. Na literatura do empreendedorismo, há comumente constructos pouco explorados ou não explorados suficientemente, como é o caso dos processos meta-cognitivos da autorrealização do indivíduo empreendedor (Akilu;Junaidu, 2015;Carland;Carland;Carland III, 1995;. Uma parte dos estudiosos trabalha o empreendedorismo como catalisador de mudanças na economia, através de inovações tecnológicas e novos processos de produção Oliveira, 2016).…”
Section: Rafael Farias Gonçalves Gustavo Henrique Silva De Souza Nilt...unclassified
“…O papel da paixão (afeto, emoção, satisfação e entusiasmo pelo que faz) como atributo inerente aos empreendedores (Cardon et al, 2005;Cardon, 2008;Cardon et al, 2013;Souza et al, 2016a) corrobora a disposição motivacional por meio da autorrealização. Na literatura do empreendedorismo, há uma gama enorme de estudos (para além dos já citados aqui) que relacionam o comportamento empreendedor à natureza da autorrealização enquanto elemento motivacional essencial para a atividade de empreender (p.ex., Akilu;Junaidu, 2015;Daros, 2005;Pang;Fu, 2019;Hashim;Othman;Abdullah, 2010;Heydari;Madani;Rostami, 2013;Jonathan;Silva, 2007;Machado;Gimenez, 2000;Schindehutte;Allen, 2006;Novitasari;Amboningtyas;Hasiholan, 2020;Parreira, 2015), embora haja poucas pesquisas empíricas de mapeamento da autorrealização em empreendedores (p.ex., Carland;Carland;Carland III, 1995;. Portanto, este capítulo avança nesse sentido.…”
Section: Autorrealização Do Empreendedorunclassified
“…Their planning is not advantageously done. SSI Units that plan strategically (compared to those that do not) are more likely to be those that achieve higher sales growth, higher returns on assets and higher profit margins (Berman, Gordon, & Sussman, 1997;Bracker, Keats, & Pearson, 1988;Carland & Carland, 2003;Gibson & Casser, 2005). Smaller units that are strategic in their approach are more innovative, and may attain higher global growth Kraus (2007) has suggested that it might be the 'right kind of planning' rather than the mere fact that formal planning is exercised which distinguishes growing enterprises from non-growing enterprises.…”
Section: Review Of Literaturementioning
confidence: 99%